PSYCHOLOGICAL PECULIARITIES OF PATIENTS WITH CHRONIC COLITIS AT THE STAGE OF REMISSION - Melnichuk, M.M.; Pavlenko, V.M. (World of Medicine and Biology, 2019)
The article analyzes the peculiarities character’s accentuation of patients with chronic colitis in remission. The types of their attitude to the disease and mechanisms of psychological defense are identified. The study shows that only 7% of patients with chronic colitis do not have problems with social adaptation caused by features of their internal picture in the disease. The overwhelming majority sooner or later face similar problems of intrapsychic orientation (5%), interpsychic orientation (15%) or their combination (73%). Significant correlations between patients’ accentuations of character, their internal picture of the disease, and mechanisms of psychological defense are revealed. The peculiarities of these parameters depending on patients’ gender and their experience of the disease are shown. Significant differences were also found for internal picture of the disease (IPD) in patients with different disease duration: patients who have been diseased less than 5 years were significantly less likely to have sensitive and self-centered IPD types, and, conversely, euphoric type was observed more frequently than in patients whose disease has lasted for over 15 years.